English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

a. 3x^2-x+5
b. 75-30x+3x^2
c. 3x^2-15x^2
d. 15x^2-3x^3

2007-01-30 01:41:59 · 5 answers · asked by lana l 1 in Science & Mathematics Mathematics

5 answers

f • g(x) = f(g(x))
= f(5 - x)
= 3(5 - x)²
= 3(25 - 10x + x²)
= 75 - 30x + 3x²

b

2007-01-30 01:47:52 · answer #1 · answered by Tom :: Athier than Thou 6 · 2 1

First: "(f ·g)(x)" means multiply the functions...

(3x^2)(5 - x)

Sec: eliminate the parenthesis - use distribution > multiply the outer term with the terms in parenthesis...

(3x^2)(5) + (3x^2)(- x)

15x^2 + (-3x^3)

15x^2 - 3x^3

Third: the solution has to be in alpha descending order...

= - 3x^3 + 15x^2

2007-01-30 12:10:18 · answer #2 · answered by ♪♥Annie♥♪ 6 · 0 0

f(x)=3x^2
g(x)=5-x
(f0g)x = 3(5-x)^2
= 3(25-10x+x^2)
= 75 -30x +3x^2 this mean no ((b))
if you want (g 0 f) =
= 5- 3x^2
thats all

2007-01-30 10:03:18 · answer #3 · answered by Khalidxp 3 · 1 0

3x^2 +x -5

f(x) - g(x)

2007-01-30 09:47:42 · answer #4 · answered by Babygirl 3 · 0 2

(f.g){x} = f{x}.g{x} (3x5)x^2-3(x^3)
d.

2007-01-30 09:53:41 · answer #5 · answered by miga 2 · 0 2

fedest.com, questions and answers